2022
DOI: 10.1002/pol.20210913
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer complexes as dual thermal/photo initiators for free‐radical frontal polymerization

Abstract: Frontal polymerization is a process in which a localized reaction zone propagates from the coupling of thermal transport and the Arrhenius rate dependence of an exothermic polymerization; monomer is converted into polymer as the front passes through an unstirred medium. Herein we report the first study of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Four main ignition categories exist for frontal free-radical polymerizations: thermal, 29,33,44,46,50,67,75,76,78,[88][89][90]92,125,132,165,[198][199][200][201][202]205 photo, [55][56][57]133,165,250,252,254,[257][258][259][260][261][262][263][264] plasma, [265][266][267] and magnetocaloric. 201,234 Thermal triggering typically involves the use of a soldering iron or oil bath to heat a localized region.…”
Section: Ignition Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Four main ignition categories exist for frontal free-radical polymerizations: thermal, 29,33,44,46,50,67,75,76,78,[88][89][90]92,125,132,165,[198][199][200][201][202]205 photo, [55][56][57]133,165,250,252,254,[257][258][259][260][261][262][263][264] plasma, [265][266][267] and magnetocaloric. 201,234 Thermal triggering typically involves the use of a soldering iron or oil bath to heat a localized region.…”
Section: Ignition Techniquesmentioning
confidence: 99%
“…Photoinitiators follow the same mechanism as that described above for epoxide ring-opening polymerizations (Section 4.2.1), where a mixture of UV-active and thermal radical sources provide more uniform radical concentrations. [55][56][57]133 Recent work from Gary et al 250 demonstrated that the inclusion of iodonium PAG salts enable both photo and thermal initiation modes with acrylate monomers.…”
Section: Ignition Techniquesmentioning
confidence: 99%
“…[19,24,25,33,34] Regarding photopolymerization resins or formulations, in addition to the typical Type I, II photoinitiators which play an important role, [21,35,36] electron donor-acceptor complexes (EDA, also known as charge transfer complexes, CTCs) are also common redox initiators often used in photopolymerization systems. [37,38] Even though the two precursors do not absorb visible light, the resulting EDA complexes often do absorb visible light, therefore the photochemistry of EDA complexes is considered to be a powerful strategy for expanding the chemical potential of visible-lightdriven radical synthesis. [39][40][41][42][43] Back in the 1950s, after 40 years of investigation, spectroscopy showed that benzene and mesitylene form 1:1 complexes of considerable stability with iodine by Benesi and Hildebrand.…”
Section: Introductionmentioning
confidence: 99%
“…Frontal polymerization (FP) is a fast and self‐sustained polymerization mode, in which only initiation energy is required to form a stable front for the reaction system, and then the propagating front rapidly converts monomers into polymers upon the intrinsic exothermic nature 23–25 …”
Section: Introductionmentioning
confidence: 99%